2009
DOI: 10.1242/jeb.032870
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific and intersexual learning rate differences in four butterfly species

Abstract: SUMMARYLearning plays an important role in food acquisition for a wide range of insects and has been demonstrated to be essential during flower foraging in taxa such as bees, parasitoid wasps, butterflies and moths. However, little attention has been focused on differences in floral cue learning abilities among species and sexes. We examined the associative learning of flower colour with nectar in four butterfly species: Idea leuconoe, Argyreus hyperbius, Pieris rapae and Lycaena phlaeas. All butterflies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…Raine and Chittka 2007) to eight, as in our study, to as many as 10 or 12 (Lunau 1990; e.g. Giurfa et al 1995;Kandori et al 2009). There are also variations in the spatial arrangements, e.g.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Raine and Chittka 2007) to eight, as in our study, to as many as 10 or 12 (Lunau 1990; e.g. Giurfa et al 1995;Kandori et al 2009). There are also variations in the spatial arrangements, e.g.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies have described spontaneous colour preferences in bees (Lunau 1990;Giurfa et al 1995;Chittka et al 2004;Dyer et al 2016), butterflies (Ilse 1928;Swihart and Swihart 1970;Weiss 1997;Kinoshita et al 1999;Kandori et al 2009;Blackiston et al 2011), moths (Kelber 1996;Goyret et al 2008), and hoverflies (Lunau and Wacht 1994). The aims of the present study were to explore a comparative approach with bees and to identify potential differences in spontaneous colour responses between temperate and tropical bees, comparing the responses of three social bee species that were tested under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species-specific differences in learning performance have been shown in many insect groups including bees, parasitoid wasps, and butterflies [29], [39]–[42]. However, natural within-species variations can affect between-species comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…For many herbivorous insects, yellow can act as a superoptimal stimulus that elicits alightment on living plants (Prokopy and Owens 1983). Although B. rapa ßower petals are yellow and P. rapae females prefer to land on yellow artiÞcial ßowers (Kandori et al 2009), we saw no evidence that the female butterßies were especially attracted to the yellowÐ green leaves or mistook the leaves for yellow ßowers and nectaring. Our landing results are similar to those reported in previous studies that have shown an innate landing preference for green foliage (SnellRood andPapaj 2009, Zheng et al 2010).…”
Section: Discussionmentioning
confidence: 66%